Perovskite solar cell and preparation method thereof
By using N-type doped PC61BM as the electron transport layer material in perovskite solar cells, the problem of insufficient conductivity of PC61BM is solved, efficient energy conversion and stability improvement is achieved, production process is simplified, and it is suitable for industrial applications.
Patent Information
- Application Number
- CN202410918885.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Among the existing perovskite solar cells, the fullerene derivative PC61BM has limited conductivity, resulting in a low thickness of the cathode interface layer and it is difficult to completely cover the perovskite surface, resulting in a reduced device stability and mismatch with the cathode energy level. The complexity of the preparation process is increased and it is difficult to meet the needs of large-scale industrial production.
Using N-type doped fullerene derivative PC61BM as the electron transport layer material, the conductivity is improved and the cathode energy level is matched, and the cathode interface modification layer is omitted to achieve thick film processing and energy. Improved conversion efficiency.
It improves the conductivity of the electron transport layer, enhances the energy conversion efficiency, simplifies the production process, is suitable for large-scale industrial production, and improves device stability, avoids direct contact between perovskites and metal electrodes.
Smart Images

Figure CN119136566A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells (PVSCs) are one of the effective ways to solve environmental pollution and energy crisis. Perovskite materials have the advantages of low exciton binding energy, long carrier diffusion length, high absorption coefficient, adjustable band gap and high carrier mobility. At present, PVSCs are considered to be a new generation of green energy technology with great industrial prospects. In the past decade, due to the continuous development of perovskite component optimization, additive engineering, passivation engineering and interface engineering, the power conversion efficiency (PCE) of solution-processed PVSCs has been greatly improved from 3.8% to 26.4%. The commonly used pin plane inverted PVSCs are composed of a photoactive perovskite layer, an electrode (including a cathode and anode), an interface (including a cathode and anode) modification layer and a transport layer (including electrons and holes). Among them, an electron transport layer (ETLs) is introduced between the photoactive layer and the cathode interface to ensure that the charge can be extracted and transferred efficiently; and it has a good match with the energy level of the perovskite layer and acts as a barrier layer for ion diffusion in the perovskite, which can improve the device performance and stability. As the commercialization of PVSCs continues to advance, its energy conversion efficiency is required to be further improved. The development of ETLs materials with high conductivity and thick film processing has become one of the important challenges facing researchers.
[0003] As a classic ETLs material, fullerene derivative PC 61 BM has limited conductivity (about 10 -8 ~10 -7 Scm -1 ), resulting in a lower thickness of the cathode interface layer, which is generally 40-50nm. 61 It is difficult for BM to completely cover the perovskite surface, so that part of the perovskite layer is in direct contact with the metal electrode. The chemical reaction between the perovskite and the metal electrode will cause the device stability to decrease. 61 BM and cathode energy levels do not match, and PC 61 The cathode interface layer is introduced between BM and cathode to improve the interface energy level arrangement and enhance electron extraction, which undoubtedly increases the complexity of the preparation process and is difficult to meet the requirements of large-area (generally 100cm 2 In order to solve the above problems, improve PC 61 The conductivity of BM and improve PC 61 The energy levels of BM and cathode are matched, so it is very meaningful to omit the cathode interface modification layer. Summary of the invention
[0004] The object of the present invention is to provide a perovskite solar cell and a method for preparing the same, aiming to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A perovskite solar cell and a preparation method thereof, comprising an anode, a hole transport layer, a photoactive layer, an electron transport layer and a cathode stacked in sequence;
[0007] The photoactive material used to prepare the photoactive layer is metal halide perovskite, which is a cubic crystal material with a molecular formula of ABX3, wherein A and B are cations and X is an anion. Specifically: A is Cs + 、MA + and FA + ; B is Pb 2 + , X is Br - and I - The specific chemical formula of the photoactive layer material is (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 ;
[0008] The electron transport material used to prepare the electron transport layer is a fullerene derivative [6,6]-phenyl-C 61 -Methyl butyrate (hereinafter referred to as PC 61 BM) or N-type doped fullerene derivative PC 61 BM (hereinafter referred to as N-type doped PC 61 BM), the N-type doped PC 61 The N-type dopant used in BM is cesium fluoride (CsF), and the PC 61 BM has the structure shown in Formula I:
[0009]
[0010] Furthermore, the material of the anode is ITO, and the material of the cathode is metal.
[0011] Furthermore, the hole transport material used to prepare the hole transport layer is nickel oxide (NiO X ) and [2-(9H-carbazol-9-yl)ethyl]phosphoric acid (2PACz).
[0012] Furthermore, the photoactive material is a cubic crystal formed by crystallization of a mixture of CsI, MABr, FAI, PbI2 and PbBr2, and the chemical molar ratio of CsI, MABr, FAI, PbI2 and PbBr2 is 0.05:0.09:0.86:0.91:0.09.
[0013] Furthermore, when the electron transport material is N-type doped PC 61 In the case of BM, the doping concentration of CsF in the electron transport layer is 0.20 to 7.40 mol%.
[0014] Furthermore, the thickness of the electron transport layer is 45 nm or 105 nm.
[0015] A method for preparing a perovskite solar cell according to the above-mentioned method comprises the following steps:
[0016] Two hole transport material solutions are coated on the surface of the anode and annealed to form a hole transport layer on the surface of the anode;
[0017] A precursor of a photoactive material solution is coated on the surface of the hole transport layer, and the solution is continuously spin-coated in two steps of low speed and high speed, and an anti-solvent is dropped on the substrate during the high-speed spin-coating step, and a perovskite film is obtained after annealing to form a photoactive layer on the surface of the hole transport layer;
[0018] coating an electron transport material solution on the surface of the photoactive layer, and forming an electron transport layer on the surface of the photoactive layer after removing the solvent;
[0019] A cathode is prepared on the surface of the electron transport layer to obtain a perovskite solar cell.
[0020] Furthermore, when the electron transport material used to prepare the electron transport layer is PC 61 When BM, the electron transport material solution is PC 61 BM solution, the PC 61 The concentration of BM solution was 20 mg / mL or 40 mg / mL.
[0021] Furthermore, when the electron transport material used to prepare the electron transport layer is N-type doped PC 61 When BM is used, the preparation steps of the electron transport material solution are as follows: 61 The chlorobenzene solution of BM was mixed with CsF isopropanol solutions of different concentrations to prepare electron transport material solutions with different doping concentrations; the PC in the electron transport layer material solution 61 The concentration of BM was 20 mg / mL or 40 mg / mL.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses N-type doped PC 61 BM is used as an electron transport layer in perovskite solar cells, which can improve the conductivity of the electron transport layer material and match the energy level of the cathode, realize thick film processing, and obtain PVSCs with enhanced energy conversion efficiency without the need for a cathode interface modification layer. It is suitable for large-scale production and can meet the needs of large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the perovskite solar cell in the present invention.
[0025] Figure 2 The PC with a thickness of 45 nm in Example 1 61 Current-voltage curves of perovskite solar cells with BM electron transport layer.
[0026] Figure 3 The PC with a thickness of 45 nm in Examples 3 to 7 61 Current-voltage curves of perovskite solar cells with BM:CsF electron transport layer.
[0027] Figure 4 PC with a thickness of 105 nm in Examples 8 to 14 61 BM electron transport layer or PC 61 Current-voltage curves of perovskite solar cells with BM:CsF electron transport layer. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0030] like Figure 1 As shown, a perovskite solar cell provided by an embodiment of the present invention includes an anode, a hole transport layer, a photoactive layer, an electron transport layer and a cathode stacked in sequence.
[0031] As a preferred embodiment of the present invention, the material of the anode is preferably indium tin oxide (ITO); the thickness of the anode is preferably 140-180 nm, more preferably 150-170 nm, and further preferably 160 nm.
[0032] As a preferred embodiment of the present invention, the hole transport layer is in contact with one side surface of the anode. The hole transport material used to prepare the hole transport layer is preferably nickel oxide (NiO X ) (CAS No. 1313-99-1) and [2-(9H-carbazol-9-yl)ethyl]phosphoric acid (2PACz) (CAS No. 20999-38-6). The hole transport layer is preferably NiO produced by Liaoning Youxuan New Energy Technology Co., Ltd., China. X The deionized water solution and the ethanol solution of 2PACz produced by Xi'an Yuri Solar Energy Technology Co., Ltd. of China were prepared. X and 2PACz as hole transport materials, denoted as NiO X / 2PACz hole transport layer. X The thickness of the hole transport is preferably 10 to 50 nm, more preferably 20 to 40 nm, and further preferably 35 nm; the thickness of the 2PACz hole transport is preferably 2 to 10 nm, more preferably 4 to 8 nm, and further preferably 7 nm.
[0033] As a preferred embodiment of the present invention, the photoactive layer is in contact with a surface on one side for hole transport. The photoactive material used to prepare the photoactive layer is a cubic crystal material generated by crystallization of a mixed solution of CsI, MABr, FAI, PbI2 and PbBr2, including inorganic halide materials and organic halide materials, the inorganic halide includes CsI (CAS No. 7789-17-5), PbI2 (CAS No. 10101-63-0) and PbBr2 (CAS No. 10031-22-8), and the organic halide material includes MABr (CAS No. 6876-37-5) and FAI (CAS No. 879643-71-7). The chemical molar ratio of CsI, MABr, FAI, PbI2 and PbBr2 is preferably 0.05:0.10:0.90:0.90:0.1, and more preferably 0.05:0.09:0.86:0.91:0.09. In an embodiment of the present invention, the photoactive layer prepared with CsI, MABr, FAI, PbI2 and PbBr2 as photoactive materials is recorded as a perovskite photoactive layer. The thickness of the photoactive layer is preferably 400 to 700 nm, more preferably 500 to 600 nm, and further preferably 550 nm. The structural formulas of CsI, MABr, FAI, PbI2 and PbBr2 are specifically shown as follows:
[0034]
[0035] As a preferred embodiment of the present invention, the electron transport layer is in contact with one side surface of the photoactive layer. The electron transport material used to prepare the electron transport layer is PC 61 BM or N-type doped PC 61 BM, the N-type doped PC 61 The N-type dopant used in BM is CsF, and the PC 61 BM has the structure shown in Formula I:
[0036]
[0037] The structural formula of the cesium fluoride is specifically shown below:
[0038] CF 。
[0039] The doping concentration of CsF in the electron transport layer is preferably 0.20-7.40 mol%, specifically 0.20 mol%, 0.79 mol%, 1.96 mol%, 3.84 mol%, 5.66 mol% or 7.40 mol%. The doping concentration of CsF here specifically refers to the amount of CsF in the ratio of CsF to PC. 61 The percentage of the total amount of BM. In the embodiment of the present invention, PC 61 The electron transport layer prepared by BM is denoted as PC 61 BM electron transport layer; PC is doped with N type 61 BM is an electron transport material (cesium fluoride is used as an N-type dopant) and the electron transport layer is denoted as PC. 61 BM:CsF electron transport layer: The thickness of the electron transport layer is preferably 20 to 150 nm, more preferably 30 to 120 nm, and further preferably 45 nm or 100 nm.
[0040] The PC 61 BM, as an electron acceptor in the low conduction band, has the ability to undergo anion-induced electron transfer reaction with alkali metal fluoride donor compounds, thereby accepting dopant electrons. 61 BM is used to prepare the electron transport layer, which can exist stably in the solution, so it is easy to achieve efficient doping through solution coating film forming technology, which can effectively improve the conductivity of the electron transport layer and match the energy level of the metal cathode, thus obtaining PVSCs with enhanced energy conversion efficiency without the need for a cathode interface modification layer.
[0041] As a preferred embodiment of the present invention, the cathode contacts one side surface of the electron transport layer. The cathode is preferably made of metal, more preferably copper; the thickness of the cathode is preferably 80 to 120 nm, more preferably 90 to 110 nm, and further preferably 100 nm.
[0042] One embodiment of the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:
[0043] Two hole transport material solutions are coated on the surface of the anode and annealed to form a hole transport layer on the surface of the anode;
[0044] A precursor of a photoactive material solution is coated on the surface of the hole transport layer, and the solution is continuously spin-coated in two steps of low speed and high speed, and an anti-solvent is dropped on the substrate during the high-speed spin-coating step, and a perovskite film is obtained after annealing to form a photoactive layer on the surface of the hole transport layer;
[0045] coating an electron transport material solution on the surface of the photoactive layer, and forming an electron transport layer on the surface of the photoactive layer after removing the solvent;
[0046] A cathode is prepared on the surface of the electron transport layer to obtain a perovskite solar cell.
[0047] In the examples of the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0048] When the material of the anode is ITO, the present invention preferably obtains the anode by magnetron sputtering coating on the substrate, and then further prepares the hole transport layer on the anode. The substrate is preferably a sodium-lime-based glass sheet. The present invention has no special requirements for the specific conditions used when magnetron sputtering the anode. The coating conditions familiar to those skilled in the art can be used to obtain an anode that meets the requirements of thickness and transmittance. The solvents in the two material solutions of the hole transport layer are preferably deionized water and anhydrous ethanol; when the hole transport material is nickel oxide (NiO X ), the hole transport material solution is preferably NiO X deionized water solution; preferably NiO X The deionized water solution was filtered through a 0.45 μm water-based polyethersulfone (PES) filter membrane before use. X The concentration is preferably 20 to 40 mg / mL, more preferably 30 mg / mL. X The coating method of the hole transport material solution is preferably dynamic spin coating, the spin coating speed is preferably 2000-4000 r / min, more preferably 3000 r / min; the spin coating time is preferably 20-60 s, more preferably 30 s. XThe hole transport layer is preferably annealed to remove the solvent; the annealing temperature is preferably 100-200°C, more preferably 150°C; the annealing time is preferably 10-20 minutes, more preferably 15 minutes. The present invention can remove the solvent in the wet film through annealing, which is beneficial to improve the stability of the perovskite solar cell. Obtain NiO X After the hole transport layer, the NiO X The hole transport layer is coated with [2-(9H-carbazole-9-yl)ethyl]phosphoric acid (2PACz) hole transport material solution, and NiO is formed on the anode surface after removing the solvent. X / 2PACz hole transport layer. When the hole transport material is [2-(9H-carbazole-9-yl)ethyl]phosphoric acid (2PACz), the hole transport material solution is preferably an anhydrous ethanol solution of 2PACz; preferably, the anhydrous ethanol solution of 2PACz is filtered through a 0.45μm polytetrafluoroethylene (PTFE) filter membrane before use. The concentration of 2PACz is preferably 0.3-1mg / mL, more preferably 0.5mg / mL. The coating method of the 2PACz hole transport material solution is preferably spin coating, and the spin coating speed is preferably 2000-4000r / min, more preferably 3000r / min; the spin coating time is preferably 30-60s, more preferably 40s. The method for removing the solvent from the 2PACz hole transport layer is preferably annealing treatment; the annealing temperature is preferably 80-150℃, more preferably 100℃; the annealing time is preferably 5-20min, more preferably 10min. The present invention can remove the solvent in the wet film through annealing treatment, thereby facilitating improving the stability of the perovskite solar cell.
[0049] The photoactive materials are all purchased from Liaoning Youxuan New Energy Technology Co., Ltd., China. The concentration of the photoactive material solution in the photoactive material solution is preferably 1 to 2M, more preferably 1.5M. The solvent in the photoactive material solution is a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the volume ratio of DMF / DMSO is preferably 3 to 5:1, more preferably 4:1, which can ensure that the photoactive material is fully dissolved. The photoactive material solution of the present invention does not require the use of additives. The coating method of the photoactive material solution is preferably spin coating, and the solution containing the photoactive material is coated on the substrate, and spin coated in two consecutive steps. The first step of the spin coating speed is preferably 800 to 1200 r / min, more preferably 1000 r / min, and the spin coating time is preferably 5 to 15s, more preferably 10s. The second step spin coating speed is preferably 4000 to 6000 r / min, more preferably 5000 r / min, and the spin coating time is preferably 20 to 40s, more preferably 30s. 5 to 10 seconds before the end of the second high-speed spin coating step, the anti-solvent chlorobenzene (CB) is quickly dripped onto the substrate, preferably 8 seconds. The temperature of the annealing treatment of the perovskite photoactive layer film is preferably 80 to 120°C, more preferably 100°C, and the annealing time is preferably 10 to 20 minutes, more preferably 15 minutes. The present invention can remove the solvent in the wet film through annealing treatment, thereby forming a photoactive layer on the surface of the hole transport layer; and the annealing treatment can change the morphology and crystallinity of the photoactive layer, forming a channel that is conducive to charge transfer and obtaining a cubic crystallized perovskite photoactive layer film, thereby improving the energy conversion efficiency of the device.
[0050] The solvent of the electron transport material solution is preferably chlorobenzene. 61 BM (purchased from Liaoning Youxuan New Energy Technology Co., Ltd., China), the electron transport material solution is preferably PC 61 BM solution, specifically PC 61 BM is dissolved in chlorobenzene; PC 61 The concentration of the BM solution is preferably 10 to 45 mg / mL, more preferably 20 mg / mL or 40 mg / mL. 61 When the N-type dopant used is CsF, the solvent of the N-type dopant CsF solution is preferably isopropanol, and the method for preparing the electron transport material solution preferably comprises the following steps: 61 The chlorobenzene solution of BM was mixed with the isopropanol solution of CsF to obtain an electron transport material solution. 61 BM and CsF were dissolved in chlorobenzene and isopropanol respectively, and then the resulting PC 61 BM solution was mixed with CsF solution and stirred for 2 h to obtain electron transport material solution; PC 61The concentration of BM is preferably 10 to 45 mg / mL, more preferably 20 mg / mL or 40 mg / mL; PC 61 The concentration and volume ratio of the BM solution to the CsF solution can ensure that the CsF doping concentration in the electron transport layer meets the requirements. The coating method of the electron transport material solution is preferably spin coating, and the spin coating speed is preferably 800 to 2000 r / min, more preferably 1200 r / min; the present invention has no special requirements for the spin coating time, and it is sufficient to ensure that the electron transport layer with a thickness that meets the requirements is obtained after the solvent in the wet film obtained after spin coating is removed.
[0051] When the cathode is made of copper, the present invention preferably deposits the cathode on the surface of the electron transport layer; the metal raw material used for the deposited cathode is a commercially available commodity known to those skilled in the art, and the present invention has no special restrictions on the form of the metal raw material, which can be metal powder, metal strip, metal sheet or metal block. The deposition speed is preferably More preferably The vacuum degree of evaporation is preferably (1.9 to 2.1) × 10 -4 Pa, more preferably 2.0×10 -4 Pa; the evaporation power is preferably 39-46W, more preferably 40-45W; the evaporation time is based on ensuring that the thickness of the cathode meets the requirements. The effective area of the perovskite solar cell is 0.1cm 2 .
[0052] Example 1: Preparation of ITO / NiO X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61 BM / Cu perovskite solar cell, the steps are as follows:
[0053] ITO with a thickness of 160 nm was obtained by magnetron sputtering on a sodium-calcium-based glass substrate as an anode;
[0054] NiO X Dispersed in deionized water solvent, the concentration is 30mg / ml. Filtered with a 0.45μm water-based polyethersulfone (PES) filter membrane, and then dynamically spin-coated on the anode surface at a speed of 3000r / min, annealed at 150℃ for 15min, forming a 35nm thick NiO on the anode surface. X Hole transport layer, ITO / NiO X Device: 2PACz was dissolved in anhydrous ethanol solvent at a concentration of 0.5 mg / ml. It was filtered through a PTFE filter membrane and then spin-coated on NiO at a speed of 3000 r / min. XThe hole transport layer surface was annealed at 100℃ for 10min. X A 2PACz hole transport layer with a thickness of 7 nm is formed on the surface of the hole transport layer to obtain ITO / NiO X / 2PACz device;
[0055] CsI, MABr, FAI, PbI2 and PbBr2 are mixed with a mixed solvent of DMF / DMSO to obtain a perovskite precursor solution. The chemical molar ratio of CsI, MABr, FAI, PbI2 and PbBr2 in the perovskite precursor solution is 0.05:0.09:0.86:0.91:0.09; the volume ratio of solvent DMF to solvent DMSO is 4:1; the concentration of the perovskite precursor solution is 1.5M. The perovskite precursor solution is added dropwise to NiO X / 2PACz hole transport layer, by two consecutive steps of spin coating (slow speed step spin coating speed 1000r / min, time 10s and high speed step spin coating 5000r / min, time 30s), the anti-solvent chlorobenzene was quickly added 8s before the end of the high speed spin coating step, followed by annealing at 100℃ for 15min, on NiO X A perovskite photoactive layer with a thickness of 550 nm is formed on the surface of the ITO / NiO / 2PACz hole transport layer. X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 Devices;
[0056] PC 61 BM was dissolved in chlorobenzene to obtain a PC concentration of 20 mg / ml. 61 BM solution. Filtered with a 0.45 μm hydrophobic PTFE filter membrane, and then spin-coated on the surface of the perovskite photoactive layer at a speed of 1200 r / min to form a PC with a thickness of 45 nm on the surface of the perovskite photoactive layer. 61 BM electron transport layer, ITO / NiO X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61 BM devices.
[0057] ITO / NiO X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ]0.95 / PC 61 The BM device is placed in the evaporation chamber. A copper metal layer with a thickness of 100 nm was evaporated on the surface of the electron transport layer as the cathode to obtain ITO / NiO X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61 BM / Cu perovskite solar cell. The effective area of this perovskite solar cell is 0.1cm 2 .
[0058] The performance of the perovskite solar cell prepared in this embodiment was tested, and the results are as follows: Figure 2 shown. Figure 2 The open circuit voltage of the perovskite solar cell is 1.112 V and the short circuit current density is 21.10 mA / cm 2 , the fill factor is 77.62%, the energy conversion efficiency of the perovskite solar cell is calculated to be 18.22%, and the series resistance is 5.461Ω·cm 2 , the parallel resistance is 3245Ω·cm 2 .
[0059] Embodiment 2: PC 61 BM was dissolved in chlorobenzene and stirred at room temperature for 12 h to obtain PC with a concentration of 20 mg / mL. 61 BM solution; CsF (purchased from Sigma-Aldrich, used directly without further purification) was dissolved in isopropanol and stirred at room temperature for 4 h to obtain a 10 mg / mL N-DMBI chlorobenzene solution; different volumes of CsF isopropanol solution were mixed with PC 61 BM solution was mixed and stirred at room temperature for 2 h to obtain CsF-doped PC with different doping concentrations. 61 BM solution.
[0060] Examples 3-7: Preparation of ITO / NiO according to the method of Example 1 X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61 BM / Cu perovskite solar cells or ITO / NiO X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3)0.10 ] 0.95 / PC 61 BM: CsF / Cu perovskite solar cell, the difference is that the electron transport material solution is CsF-doped PC 61 BM solution. CsF-doped PC 61 PC in BM solution 61 BM concentration was 20 mg / mL, CsF-doped PC 61 The doping concentrations of CsF in the BM solution were 0.30 mol% (Example 3), 0.89 mol% (Example 4), 1.19 mol% (Example 5), 1.48 mol% (Example 6), and 2.91 mol% (Example 7); and the obtained PC 61 The thickness of BM:CsF electron transport layer is 45nm. 61 The BM solution was prepared according to the method of Example 2 (the relevant concentration can be adaptively adjusted to ensure that the required concentration of CsF-doped PC is obtained). 61 BM solution).
[0061] The performance of the perovskite solar cells prepared in Examples 3 to 7 was tested. The results are as follows: Figure 3 The specific data are listed in Table 1.
[0062] Table 1 Performance test data of perovskite solar cells prepared in Examples 3 to 7
[0063]
[0064]
[0065] Depend on Figure 3 Compared with Table 1, it can be seen that CsF doped PC 61 BM as an electron transport layer is beneficial to improve the short-circuit current density and fill factor, and reduce the series resistance, thereby improving the energy conversion efficiency of perovskite solar cells. 61 The optimal doping concentration of BM solution is 0.89mol% (mass fraction is 0.15wt%). In the absence of cathode interface modification layer and simplified device structure, an energy conversion efficiency as high as 20.09% is obtained.
[0066] Examples 8-14: Preparation of ITO / NiO according to the method of Example 1 X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61BM / Cu perovskite solar cell; ITO / NiO prepared according to the method of Example 3 X / 2PACz / (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 / PC 61 BM: CsF / Cu perovskite solar cells, the difference is that CsF doped PC 61 PC in BM solution 61 The BM concentration was 40 mg / mL, and the PC 61 The thickness of BM:CsF electron transport layer is 105nm; CsF doped PC 61 The doping concentrations of CsF in the BM solution are 0% (Example 8), 0.20 mol% (Example 9), 0.79 mol% (Example 10), 1.96 mol% (Example 11), 3.84 mol% (Example 12), 5.66 mol% (Example 13) and 7.40 mol% (Example 14). 61 BM solution was prepared according to the method of Example 2 (the relevant concentration can be adjusted adaptively to ensure that the required concentration of CsF-doped PC is obtained). 61 BM solution).
[0067] The performance of the perovskite solar cells prepared in Examples 8 to 14 was tested. The results are as follows: Figure 4 The specific data are listed in Table 2.
[0068] Table 2 Performance test data of perovskite solar cells prepared in Examples 8 to 14
[0069]
[0070]
[0071] Depend on Figure 4 As shown in Table 2, the open circuit voltage of the perovskite solar cell prepared in Example 8 is 1.111 V, and the short circuit current density is 19.62 mA / cm 2 , the fill factor is 76.58%, and the calculated series resistance is 6.471Ω·cm 2 , the parallel resistance is 3265Ω·cm 2 , the energy conversion efficiency is 16.58%; the open circuit voltage of the perovskite solar cell prepared in Example 12 is 1.086V, and the short circuit current density is 21.78mA / cm 2 , the fill factor is 80.53, and the calculated series resistance is 3.982Ω·cm 2, the parallel resistance is 4363Ω·cm 2 , the energy conversion efficiency is 19.04%. This shows that in perovskite solar cells with Cu as cathode, CsF doped PC 61 BM as an electron transport layer, when the thickness is 105nm, not only helps to improve the short-circuit current density, fill factor and parallel resistance, but also reduces the series resistance, thereby improving the energy conversion efficiency of perovskite solar cells. 61 The optimal doping concentration of BM solution is 3.84mol% (mass fraction is 0.5wt%). In the case of no cathode interface modification layer and simplified device structure, an energy conversion efficiency as high as 19.04% is obtained.
[0072] In summary, the present invention is based on CsF doped PC 61 BM was used to prepare electron transport layers and applied to trications (such as (CsPbI3) 0.05 [(FAPbI3) 0.90 (MAPbBr3) 0.10 ] 0.95 ) in perovskite solar cells, the conductivity of the electron transport layer can be effectively improved, and PC 61 The thickness of the BM electron transport layer is extended to 105nm, which simplifies the device structure and omits the cathode interface modification layer while still ensuring that the perovskite solar cell has a high energy conversion efficiency, which can simplify the industrial production process. In addition, the high thickness of the electron transport layer effectively physically isolates the direct contact between the perovskite and the metal electrode, and acts as a barrier layer to enhance the stability of the perovskite solar cell. The doping method is very simple, and only requires mixing the isopropanol solution of CsF and PC 61 The chlorobenzene solution of BM is mixed evenly to achieve the doping effect. In the prior art, most N-type dopants are doped by vacuum thermal evaporation technology, which generates a high temperature during the evaporation process, which has an adverse effect on the energy conversion efficiency and stability of the device. In addition, the vacuum evaporation technology used in industry is costly, while the present invention achieves doping by solution coating film forming technology, which is simple, efficient and low in cost.
[0073] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A perovskite solar cell, characterized in that: It includes an anode, a hole transport layer, a photoactive layer, an electron transport layer and a cathode which are stacked in sequence; The photoactive material used to prepare the photoactive layer is metal halide perovskite, which is a cubic crystal material with a molecular formula of ABX3, wherein A is Cs + 、MA + and FA + ; B is Pb 2+ , X is Br - and I - ; The electron transport material used to prepare the electron transport layer is a fullerene derivative PC 61 BM or N-type doped fullerene derivative PC 61 BM, the N-type doped fullerene derivative PC 61 The N-type dopant used in BM is CsF, and the fullerene derivative PC 61 BM has the structure shown in Formula I:
2. The perovskite solar cell according to claim 1, characterized in that The material of the anode is ITO, and the material of the cathode is metal.
3. The perovskite solar cell according to claim 1, characterized in that: The hole transport material used to prepare the hole transport layer is NiO X and 2PACz.
4. The perovskite solar cell according to claim 1, characterized in that: The photoactive material is a cubic crystal formed by crystallization of a mixture of an inorganic halide salt, an organic halide salt and a metal halide salt.
5. The perovskite solar cell according to claim 1, characterized in that: When the electron transport material is an N-type doped fullerene derivative PC 61 In the case of BM, the doping concentration of CsF in the electron transport layer is 0.20 to 7.40 mol%.
6. The perovskite solar cell according to claim 1, characterized in that: The thickness of the electron transport layer is 45 nm or 105 nm.
7. A method for preparing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: Two hole transport material solutions are coated on the surface of the anode and annealed to form a hole transport layer on the surface of the anode; A precursor of a photoactive material solution is coated on the surface of the hole transport layer, and the solution is continuously spin-coated in two steps of low speed and high speed, and an anti-solvent is dropped on the substrate during the high-speed spin-coating step, and a perovskite film is obtained after annealing to form a photoactive layer on the surface of the hole transport layer; coating an electron transport material solution on the surface of the photoactive layer, and forming an electron transport layer on the surface of the photoactive layer after removing the solvent; A cathode is prepared on the surface of the electron transport layer to obtain a perovskite solar cell.
8. The preparation method according to claim 7, characterized in that: When the electron transport material used in preparing the electron transport layer is a fullerene derivative PC 61 In BM, the electron transport material solution is a fullerene derivative PC 61 BM solution, the fullerene derivative PC 61 The concentration of BM solution was 20 mg / mL or 40 mg / mL.
9. The preparation method according to claim 7, characterized in that: When the electron transport material used in preparing the electron transport layer is an N-type doped fullerene derivative PC 61 When BM is used, the preparation steps of the electron transport material solution are as follows: 61 The chlorobenzene solution of BM was mixed with CsF isopropanol solutions of different concentrations to prepare electron transport material solutions with different doping concentrations; the fullerene derivative PC in the electron transport layer material solution 61 The concentration of BM was 20 mg / mL or 40 mg / mL.
Citation Information
Patent Citations
Organic electroluminescent device and preparation method thereof
CN104183740A
Optimized crystallization method for hole transport layer of flexible high-efficiency large-area perovskite solar cell
CN117794333A
